Rapidly rising diabetes and increasing body weight: a counterfactual analysis in repeated cross-sectional nationally representative data from Bangladesh - Wetzel, Sarah; Sarker, Malabika; Hasan, Mehedi; Talukder, Animesh; Sudharsanan, Nikkil; Geldsetzer, Pascal (Epidemiology, 2023)
Background: - Diabetes is a growing concern in South Asia but few nationally representative studies identify factors behind this rising disease burden. We studied the nationwide change in diabetes prevalence in Bangladesh, subpopulations disproportionately affected, and the contribution of rising unhealthy weight to the change in diabetes prevalence. - Methods: - Based on a sample of 13,959 adults aged 35 years and older with biomarker measurements from the 2011 and 2017/2018 Bangladesh Demographic and Health Surveys, we estimated how the prevalence of diabetes changed nationally and across socioeconomic/geographic groups. Using counterfactual decomposition, we assessed how much the prevalence of diabetes would have grown if body mass index (BMI) had not changed between 2011 and 2017. - Results: - Diabetes prevalence increased from 12.1% (11.1, 13.1) to 14.4% (13.3, 15.5) between 2011 and 2017/2018. Diabetes grew disproportionately quickly among population groups with higher household wealth, and more education, and in three regions. Over this same period, mean BMI increased from 20.9 (20.8, 21.1) to 22.5 kg/m2 (22.4, 22.7) and overweight from 25.8 (24.4, 27.3) to 42.1% (40.4, 43.7). Under the counterfactual scenario of constant BMI, diabetes would have risen by only 1.0 (−0.4, 2.4) instead of 2.3 percentage points (0.8, 3.7) nationally, corresponding to a contribution of 58% (−106.3, 221.7). Similarly, group-specific trends were largely attributable to increasing BMI. - Conclusions: - Diabetes prevalence in Bangladesh has increased rapidly between 2011 and 2017/2018. Decomposition analysis estimates have wide confidence intervals but are consistent with the hypothesis that this change was driven by the dramatic rise in body weights.
Gesehen am 06.10.2023